Crystal Structure, Magnetic Susceptibility, and ESR Measurement of BaCu2(PO4)2 - Aripin Aripin; S. Mitsudo; T. Idehara; M. Mekata (Jurnal Matematika & Sains, 2003)
The crystal structure of BaCu2(PO4)2 has been refined from X-ray powder data. BaCu2(PO4)2 crystallizes into a triclinic structure which belongs to the space group P-1, which unit cell constant a = (9.226Â±0.023)(1) Ã, b = (9.271Â±0,018)(1) Ã, c = (10.516Â±0,09)(1) Ã, Î± = (106.76Â±0.12)(5)o, Î² = (101.65Â±0.16)(5)o, Î³ = (115.70Â±0.3)(5)o, V = (717.96Â±0.05) Ã3, Z = 4, and dcal = 4.20 g.cm-3. The copper atoms constitute isolated magnetic chains parallel to the [001] direction. The magnetic susceptibility measurement was preformed at temperatures ranging from 4.2 K to 300 K. The magnetic susceptibility shows a broad maximum at around 60 K. The magnetic susceptibility has been interpreted in terms of one-dimensional magnetic system. The temperature dependence of the magnetic susceptibility indicated a good agreement with ladder configuration model. In the ESR measurements, clear electron spin resonance (ESR) was observed. The integrated intensity has a broad maximum at around 60 K, which is consistent with the susceptibility result. A quantitative description gives resonance is the first triplet state of the excitation spectrum of ladder configuration.